Loading presentation...

Present Remotely

Send the link below via email or IM

Copy

Present to your audience

Start remote presentation

  • Invited audience members will follow you as you navigate and present
  • People invited to a presentation do not need a Prezi account
  • This link expires 10 minutes after you close the presentation
  • A maximum of 30 users can follow your presentation
  • Learn more about this feature in our knowledge base article

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

DeleteCancel

Solving quadratics by factorising

No description
by

Mr Mattock

on 4 July 2016

Comments (0)

Please log in to add your comment.

Report abuse

Transcript of Solving quadratics by factorising

Solving factorised quadratics
Starter
Write down all pairs of numbers
a
and
b
so that:

(a) a x b = 12

(b) a x b = 20

(c) a x b = 60

(d) a x b = 0
Activity
Solve the factorised quadratics on the sheet.
Solving factorised quadratic equations
x(x - 2) = 0

(x + 2)(x - 3) = 0

2x(x + 3) = 0

(2x - 3)(3x + 2) = 0
L.O. - To solve quadratics that are factorised.
Starter
Write down all pairs of numbers
a
and
b
so that:

(a) a x b = 12 YOU CANT

(b) a x b = 20 YOU CANT

(c) a x b = 60 YOU CANT

(d) a x b = 0 either
a
= 0 or
b
= 0
Solving factorised quadratic equations
x(x - 2) = 0

(x + 2)(x - 3) = 0

2x(x + 3) = 0

(2x - 3)(3x + 2) = 0
x = 0 and x - 2 = 0
x = 0 and x = 2
x + 2 = 0 and x - 3 = 0
x = -2 and x = 3
2x = 0 and x + 3 = 0
x = 0 and x = -3
2x - 3 = 0 and 3x + 2 = 0
x = 3/2 and x = -2/3
Activity
Solve the factorised quadratics on the sheet.
(1) n = -5 and n = 7
(2) n = - 6
(3)t = - 3 and t = - 5
(4) t = - 4
(5) m = - 4
(6) m = - 10 and m = 2
(7) b = - 3 and b = 7
(8) b = 2
(9) w = 3 and w = - 27
(10) w = - 9 and w = 9
(11) n = - 3
(12) n = - 3
(13) f = - and f = -

(14) f = - and f = -

(15) t = and t = 1
(16) t=

2
5
1
6
2
15
1
2
3
5
4
5
Plenary
Expand the following:

(a) x(x - 3)

(b) 2x(4 - x)

(c) (x + 2)(x - 3)

(d) (x - 5)(x - 7)
Plenary
Expand the following:

(a) x(x - 3)
= x - 3x

(b) 2x(4 - x)
= 8x - 2x

(c) (x + 2)(x - 3)
= x - x - 6

(d) (x - 5)(x - 7)
= x -12x + 35
2
2
2
2
Activities
Activity
Answers

Key
Examples

Worked
Example
Full transcript